MANAJEMEN KONFLIK DALAM PERSPEKTIF DUNIA PENDIDIKAN - Amin Setio Lestiningsih (Universitas Bina Sarana Informatika, 2011)
These days we often hear and watch the news informed about the brawl-brawl in the world ofeducation. Conflicts may be triggered by the problems that are sometimes very trivial, such issuesare not clear from the beginning but able to trigger emotions to students who are academicproblems, such as admissions, tuition, campus security, extortion, corruption and other other. Theimpact of this conflict is so great of them damaged the credibility of the campus, lecture facilitiesdamaged and even loss of life due to physical contact which in fact do the actual conflict can beaddressed and it can dimanage well be a positive thing if each individual has the ability good incommunication so that miscommunication could be avoided.Keywords: Education, Conflict Management